Analysis of non-linear degradation over NOMA-GFDM communications systems - Ccapa Gaimes, Alberth Steve (2024)
Generalized frequency division multiplexing (GFDM) and non-orthogonal multiple access (NOMA) schemes are currently regarded as promising techniques for meeting the requirements of sixth-generation (6G) communication systems. While significant attention has been devoted to studying these techniques, specific scenarios still need to be explored. Considering that one essential aspect of any communication system is the utilization of high-power amplifiers, which are typically modeled as non-linear systems, in this paper, we propose a novel methodology to analyze the bit error probability (BEP) of NOMA-GFDM systems operating on memoryless non-linear system. To account for the non-linear distortions induced by high-power amplifiers, a polynomial model is employed, and new theoretical expressions are developed to compute the BEP of the system. Specifically, exact BEP expressions for a two-user downlink NOMA-GFDM system are provided. The numerical results obtained demonstrate that non-linear distortion significantly degrades system performance.